Failures in Protein Clearance Partly Underlie Late Onset Neurodegenerative Diseases and Link Pathology to Genetic Risk - Hardy, John (Frontiers in Neuroscience, 2019)
As we identify the loci involved in late onset neurodegenerative disease we are finding that the majority of them are involved in damage response processes. In this short review I propose that it is a largely failure in these damage response processes which underly late onset disease and that the resultant pathology is a marker of the type of damage response which has failed: microglial clearance of damaged neuronal membranes in Alzheimer’s disease, ubiquitin proteasome clearance in the tauopathies, and lysosomal clearance in Parkinson’s disease